Dams, sediment discontinuity, and management responses - Kondolf, G. Mathias (IAHR, 2020)
This article focuses on the effects of sediment trapping by dams and planning/management opportunities to minimize these impacts and to restore downstream sediment supply to maintain or restore geomorphic and ecological conditions. It is complementary to other articles in this issue (e.g. Annandale et al., Efthymiou et al.), which explore structural and management approaches to reduce sediment trapping by dams, from a perspective of improving the sustainability of reservoir storage capacity for future generations.